Research of Straight Bevel Gear Modeling based on Back Cone Tangent Plane Method - Hou Hongling (Jixie chuandong)
With the development of manufacturing industry informatization,the gear product modeling is particularly important,it is the basis of analyzing the gear mesh performance.The actual tooth profile of straight bevel gear is plane involutes on its big end back cone tangent plane,because of the theory of involutes spherical design and manufacturing difficulty.For bevel gear product consistency in modeling,design and manufacturing,by using the equivalent teeth number method,involutes parametric equation is established on straight bevel gear big end back cone tangent plane through coordinate transformation.The straight bevel gear model is established by using this method.The modeling process is simplified.The modeling accuracy is satisfied design and manufacturing by analysis.